EVALUATION OF MARKETING STRATEGIES OF FINANCIAL-CREDIT ORGANIZATION IN THE CONDITIONS OF ECONOMIC INSTABILITY - Vitaly Zhuravel; Rustam Ustaev; Natalia Kharchenko (Вестник Северо-Кавказского федерального университета, 2022)
The article analyzes the marketing strategy of a financial and credit organization in modern conditions. The possible schedule of implementation of the international marketing strategy of the financial and credit organization focused on attraction of large clients and increase of the profit providing its development and timely adaptation to change of needs of economy and scientific and technical progress is presented. Moderately optimistic, moderately pessimistic and realistic options for planned growth of income (cost reduction) and costs from the implementation of the marketing strategy of the financial and credit institution are presented. The article presents the planned segment structure of income and expenses of the inancial and credit institution for 2022 after the implementation of the marketing strategy.